INFLUENCE OF IMMUNOSUPPRESSIVE AND GENETICALLY ENGINEERED THERAPY WITH TNF -alpha INHIBITOR INFLIXIMAB ON MINERAL DENSITY OF BONE TISSUE IN PATIENTS WITH JUVENILE ARTHRITIS - A.O. Lisitsyn; E.I. Alexeeva; S.I. Valieva; T.M. Bzarova; R.V. Denisova; A.M. Chomakhidze; K.B. Isaeva ("Paediatrician" Publishers LLC, 2010)
The article presents results of a study of mineral density of bone tissue in patients with juvenile arthritis treated with immunosuppressive agents and blocker of tumor necrotizing factor (TNF) alpha infliximab. Administration of immunosuppressants is unfavorable factor of osteoporosis development in all types of juvenile arthritis. Therapy with infliximab combined with methotrexate provided normalization of Z-score in patients with «early» arthritis and osteopenia (р < 0.01), and its increase in patients with «late» arthritis and osteoporosis (р < 0.001). Treatment with methotrexate, cyclosporine and prednisolone induced its decrease (р < 0.01). Obtained data proved the fact that early administration of genetically engineered biological agent allows prevention of serious complication of juvenile arthritis - systemic osteoporosis. Key words: juvenile arthritis, mineral density of bone, osteoporosis, immunosuppressants, infliximab. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(4):27-33)